2011
DOI: 10.4161/psb.6.7.15551
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution impedes plant-to-plant communication, but what is the signal?

Abstract: Since the first reports that undamaged plants gain defensive benefits following exposure to damaged neighbors, the idea that plants may signal to each other has attracted much interest. There has also been substantial debate concerning the ecological significance of the process and the evolutionary drivers. Part of this debate has centered on the distance over which signaling between plants occurs in nature. In a recent study we showed that an ozone concentration of 80 ppb, commonly encountered in nature, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Elevated ozone eliminated the associational susceptibility, with P. xylostella not displaying a preference for either receiver plant. In earlier studies, it was shown that elevated ozone concentrations significantly reduce the distance of active plant–plant signalling in lima bean (Blande et al ., , ). It was reasoned that ozone could influence the between‐plant signalling process at one or more of three junctures.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ozone eliminated the associational susceptibility, with P. xylostella not displaying a preference for either receiver plant. In earlier studies, it was shown that elevated ozone concentrations significantly reduce the distance of active plant–plant signalling in lima bean (Blande et al ., , ). It was reasoned that ozone could influence the between‐plant signalling process at one or more of three junctures.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation and formation of new products can alter the composition and ratio of key components in VOC profiles that reduce insect host location efficiency (Blande, Li, & Holopainen, 2011;Li, Blande, & Holopainen, 2016). All of these factors add a degree of complexity to the group of VOCs released as compared to the constitutive volatiles (Douma, Ganzeveld, Unsicker, Boeckler, & Dicke, 2019).…”
Section: Plant-plant Communications In the Complex Volatile Environmentioning
confidence: 99%
“…Ozone can have significant negative impacts on plant reproductive success via its negative impacts on plant tissues and plant physiology (Bergweiler & Manning, ; Black et al ., ). Furthermore, many recent studies have reported that ozone and other common oxidative pollutants, such as hydroxyl and nitrate radicals, affect the emissions of VOCs from plants and the interactions they mediate (Pinto et al ., , ; McFrederick et al ., ; Blande et al ., , ; Fuentes et al ., ). Tropospheric ozone can affect plant emissions and their effectiveness in two ways: first, by affecting plant physiology and inducing changes in the emission profiles (Andermann et al ., ; Peñuelas & Llusia, ; Holopainen & Gershenzon, ), and second, by mixing and reacting with the emitted compounds once they are released (Holopainen & Blande, ; Blande et al ., ).…”
Section: Introductionmentioning
confidence: 99%